2004
DOI: 10.1093/humrep/deh448
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of reproductive ageing patterns by hormonal and ultrasonographic ovarian reserve tests

Abstract: The pattern of reproductive ageing as assessed by hormonal and ultrasonographic OR tests does not appear to show an abrupt change at a certain age, but follows a continuously increasing rate of decline in the third decade of life. The changes in serum FSH levels and ultrasonographic OR tests follow a quadratic model in regularly menstruating women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 28 publications
2
15
0
4
Order By: Relevance
“…The central hypothesis is that the number of primordial follicles and the quality of oocyte cells in the ovaries decrease gradually [39, 40]. In this accelerated ovarian aging model, the number of primordial follicles was substantially decreased, whereas the number of atretic follicles was significantly increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The central hypothesis is that the number of primordial follicles and the quality of oocyte cells in the ovaries decrease gradually [39, 40]. In this accelerated ovarian aging model, the number of primordial follicles was substantially decreased, whereas the number of atretic follicles was significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian stimulation was shown to impact granulosa cell apoptosis and biological aging of the ovary [64-66]. Ovarian granulosa cell apoptosis is an important marker of ovarian aging [39]. The results of TUNEL fluorescence staining showed that apoptotic granulosa cells increased in ovarian follicles in ovaries that underwent consecutive superovulation compared to those of the control group, suggesting that follicular degeneration is accelerated by consecutive superovulation.…”
Section: Discussionmentioning
confidence: 99%
“…Others report moderate to high repeatability or correlations in number of antral follicles at emergence of two consecutive follicular waves (Singh et al, 2004) or following ultrasound-guided needle aspiration of antral follicles at various intervals in individual cattle (Boni et al, 1997), and from one menstrual cycle to the next in human beings (Scheffer et al, 1999). In addition, repeatability of follicle numbers during waves remains very high in individual cattle for at least 1 year (Burns et al, 2005), and others report numbers of growing preantral and antral follicles remain relatively constant until cattle are 7-9 years old (Erickson, 1966a;Katska and Smorag, 1984) and human beings are 35-40 years old (Gougeon et al, 1994;Scheffer et al, 1999;Tufan et al, 2004). Taken together, these observations imply that numbers of antral follicles during waves may remain relatively constant during extended periods of ovarian aging in individuals, despite significant loss of primordial follicles in the ovarian reserve.…”
Section: Discussionmentioning
confidence: 99%
“…Female aging has many effects on endocrine parameters and body composition caused by a gradual depletion of the primordial follicle pool (2)(3)(4)(5). The diminishing pool of growing antral follicles results in decreasing serum levels of anti-Mullerian hormone (AMH), inhibin B, and E 2 .…”
mentioning
confidence: 99%